Racism, Nationalism and Right-Wing Extremism Online: The Austrian Presidential Election 2016 on Facebook - Fuchs, Christian (Momentum Quarterly, 2016)
The 2016 Austrian presidential election saw a run-off between the Green party candidate Alexander Van der Bellen and the Freedom Party of Austria’s (FPÖ) far-right candidate Norbert Hofer. This paper asks: How did voters of Hofer express their support on Facebook? It presents the results of a qualitative ideology analysis of 6755 comments about the presidential election posted on the Facebook pages of FPÖ leader Heinz-Christian Strache and FPÖ candidate Hofer. The results reveal insights into the contemporary political role of the online leadership ideology, online nationalism, new racism online, the friend/enemy-scheme online, and online militancy. Right-wing extremism 2.0 is a complex problem that stands in the context of contemporary crises and demagoguery.